A proposed packet scheduling scheme for real-time multimedia applications in Long Term Evolution - Advanced (LTE-A) - Arafa, Mohammed H A (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Real time applications with strict Quality of services (QoS) are quite popular among cellular users, whereas delay sensitive applications require an advanced technology to adopt them. This is where Long Term Evolution-Advanced (LTE-A) comes and fulfil this requirement. LTE-A is the top leading Fourth Generation (4G) technology. It provides a speed of 3Gbps and 1.5 Gbps in downlink and uplink respectively. With this ever evolving technology the need for improvements is required. Packet scheduling is one of the important key features of LTE-A, where it dictates user selection and transmission of those user's packets based on the priority of the users to reach the receiver end correctly. Packet scheduling is one mean to achieve those QoS requirements that real-time applications require. Example of these algorithms are HARQ Aware Scheduling Algorithm (HAS), Retransmission Aware Proportional Fair Algorithm (RAPF), Chase Combining Based Max C/I Scheduling and Maximum- Largest Weighted First algorithm (M-LWDF). Although this algorithms are efficient, their performance needs to improved for real-time multimedia applications be M-LWDF is one of the best algorithm in LTE-A which was chosen to be further investigated to support QoS in high mobility environment. Packet Loss Ratio (PLR), Mean User Throughout and Fairness performance measures were used to validate the performance of M-LWDF algorithm against other algorithms using similar mobile environment. Simulation results indicate the capability of M-LWDF algorithm within the threshold of the performance measures against other benchmarks where it has demonstrated more efficiency to support and improve the performance of real-time multimedia traffic.